Análise dos perfis metabólicos de porta-enxertos de Vitis sp cocultivados com o fungo Fusarium oxysporum como estratégia para seleção de biomarcadores - Costa, Igor Rafael Sousa (2022)
The vine is a widespread fruit tree susceptible to many diseases caused by fungi such as Fusarium oxysporum. The search for tolerant rootstocks genotypes and has become a strategy to minimize this problem. Thus, the main goal of this work was to study the primary metabolism modulation of two rootstocks Pausen 1103 and BDMG573 co-cultured with F. oxysporum. Undirected global metabolomics identified biochemical markers of the early, medium, and late times (0, 4, and 8 days after infection - DAT). In the shoots, there was an overlapping between the CNT and FUS treatments of BDMG573 genotype at 0DAT and a better distinction at 4DAT and 8 DAT (15 and 20 significant metabolites). In P1103, there was a better distinction between treatments at 0 DAT (21 metabolites), followed by overlapping at 4 DAT and 8 DAT. In the roots, similarities between the two treatments of each genotype occurred at 0 DAT. Otherwise, there are distinct profiles between CNT and FUS of BDMG573 (28 and 32 metabolites) and P1103 (16 and 26 metabolites) at 4 DAT and 8 DAT, respectively. OPLS-DA multivariate analysis identified 1,3-dihydroxyacetone (at 0 and 4 DAT) and maltose (at 4 and 8 DAT) as potential biomarkers in the BDMG573 shoots. While in the shoots of P1103, some organic acids stand out at 0 DAT (glyceric acid), amino acids at 4 DAT (proline), and carbohydrates at 8 DAT (Sorbitol). In the roots of BDMG573, the metabolites β-alanine (at 0 DAT) and cellobiose and sorbitol (at both 4 and 8 DAT) stand out as potential biomarkers of Fusarium co-culture. While in the roots of P1103, the potential discriminants were carbohydrates such as galactose (at both 0 and 4 DAT) and 1,3-dihydroxyacetone (at 8 DAT). The pathways showed a increase of amino acids, glycolise, and components particularly in shoots of Pausen P1103 at all times evaluated. Overall, this work provides a new perspective of the primary metabolism modulation of tolerant and sensitive grapevine genotypes to the fungus F. oxysporum. Thus, it may contribute to assisted selection strategies for increasing genotypes tolerance and the early identification of the disease.